Large-area patterned 2D conjugated microporous polymers via photomask-assisted solid-state photopolymerization. Issue 27 (28th June 2018) - Liu, Zhengdong; Yin, Yuhang; Xiu, Fei; Wang, Xiangjing; Ju, Shang; Song, Mengya; Chang, Qing; Chen, Jie; Liu, Juqing; Huang, Wei
Abstract : Large-area patterned 2D conjugated microporous polymers (2D CMPs) were directly grown on SiO2 /Si or reduced graphene oxide (rGO) surfaces with controllable film thickness and shape. Abstract : The large-area and scalable patterning process of conjugated polymers is a critical step toward their practical applications in organic electronics. Here we report a wafer-scale patterning method for 2D conjugated microporous polymer (CMP) films on arbitrary substrates via photomask-assisted solid-state photopolymerization under ambient conditions. 2D CMP patterns from monomeric carbazole materials were controllably prepared with variable geometries with the geometric photomasks and desired film thicknesses by modulating the polymerization time. Moreover, 2D CMP patterns with various size and shapes can be formed onto a reduced graphene oxide (rGO) substrate to construct 2D CMP/rGO heterostructures. The obtained heterostructure exhibited a p-type behavior compared to the metal-like property of the rGO film. Combining this solid-state photopolymerization with photomask techniques, a patterned 2D organic/inorganic heterostructure with a precise size and shape control could be further realized for other 2D materials and their integrated devices.